Multisensory Character Education: Enhancing Social–Emotional Development in Early Childhood through Experiential Learning - Ika Anggraheni; Devi Wahyu Ertanti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Character education in early childhood is often dominated by verbal instruction, which may limit children's ability to internalize moral values through lived experience. This study explores the potential of multisensory character education—an approach that engages visual, auditory, kinesthetic, and tactile senses—to enhance social–emotional development among young learners in Indonesia. A quantitative descriptive survey was conducted with 20 early childhood teachers at RA Al Jihad, Malang. A 30-item Likert-scale questionnaire measured three constructs: multisensory character education, children’s social development, and emotional development. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. Teachers reported high levels of multisensory implementation (M = 4.21), with similarly high ratings for children’s social (M = 4.18) and emotional (M = 4.09) development. A strong positive correlation was found between multisensory character education and social–emotional outcomes (r = 0.683, p 0.01), with 46.6% variance explained (R² = 0.466). These findings suggest that multisensory strategies, grounded in experiential learning and sociocultural theory, effectively promote empathy, cooperation, and emotional regulation. This study expands current literature by demonstrating that multisensory learning supports not only cognitive but also affective and behavioral development in early childhood. Practical implications point to the need for more sensory-rich, child-centered pedagogies in character education programs.